Comunicación interna en atención primaria - Ballvé Moreno, José Luis (Aten Primaria, 2008)
OBJECTIVES: To study internal communication between primary care health professionals DESIGN: Cross-sectional, descriptive. SETTING: Catalan Health Institute Costa de Ponent Primary Care Area, Spain. PARTICIPANTS: All workers in the area (n=3565). MEASUREMENTS: Three part questionnaire: a) sociodemographic questions; b) questions scoring from 0 to 10 the current importance and operation of certain aspects; and c) questions on new communication tools. RESULTS: Of those sent a questionnaire, 39% (n=1388) responded, with a mean age of 43.2 years (95% CI, 42.75- 43.65), 28.9% being male. The major differences between importance and current events were said to be “to be informed of projects before they appear in the communication media,” “by official routes and not by rumour,” and “to be aware of projects of other teams.” The least communicated within teams. The doctors considered upward communication to be more important. Doctors are those who appreciate communication within teams better and the professionals of the users services unit (UAU) less so. Doctors are the ones who give more importance to being informed of projects at the time. 55% do not use the intranet, mainly due lack of time. The second reason is that they find it difficult. Sixty-two per cent read e-mail >2-3 times per week. Eighty-nine per cent want an electronic bulletin. The older workers use new technologies less. CONCLUSIONS: Downward, upward, and sideways communication needs to be improved, particularly upwards by doctors, and that of the teams for the UAU professionals. Intranet tools must be provided that make the work easier and training in handling new technologies must be offered.